2014
DOI: 10.11648/j.avs.20140205.12
|View full text |Cite
|
Sign up to set email alerts
|

Serologic and Virologic Investigation of BHV-1, BVDV and BHV-4 in Cattle with Metritis

Abstract: Abstract:The purpose of the present study was to evaluate the possible effects of Bovine Herpes virus-1 (BHV-1), Bovine Viral Diarrhea Virus (BVDV), and Bovine Herpes virus-4 (BHV-4) involving metritis in the selected unvaccinated dairy cattle herds in Afyon province of Turkey by serologically and virologically methods. A total of 63 dairy cattle with metritis were sampled in order to investigate the presence of BHV-1, BVDV and BHV-4 infections. The sera samples were tested for presence of antibodies to BHV-1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Despite this assumption, a wide variety of clinical symptoms including dermatitis, mastitis, vascu-litis, respiratory tract disorders, has also been declared in previous reports by some researchers. [1][2][3][4][5][6][7][11][12][13][14][15][16][17] One of them, a case report by Bellino et. al 4 1,7,11,12,[15][16][17] Pathoclinical linking remains to be elucidated by further detailed analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite this assumption, a wide variety of clinical symptoms including dermatitis, mastitis, vascu-litis, respiratory tract disorders, has also been declared in previous reports by some researchers. [1][2][3][4][5][6][7][11][12][13][14][15][16][17] One of them, a case report by Bellino et. al 4 1,7,11,12,[15][16][17] Pathoclinical linking remains to be elucidated by further detailed analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Both studies have revealed that almost all Turkish BHV-4 sequences belonged to Genotype I. [11][12][13][14][15][16][17]26 Molecular data from previous studies were limited and not eligible rather than serological ones, thus, its comparison could not be comprehensively conducted in phylogenetic and recombination analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation